Perspectives on finance, banking, and economic policy in Nigeria - Olashore, Oladele (Ibadan : Heinemann Educational Books Ltd., 1988)
This book is a collection of selected essays and public speeches made by the author during his past decade of his career in the Nigerian Financial System.
Includes bibliographical references and index.
osa 31/10/16, ijb 13/03/2019
Loan
Keywords: Financial institutions; Banks and banking; Finance, Public; Nigeria